Antibacterial and antioxidant activities of sugarcane molasses ethanolic extract and its bacteriostatic mechanisms against selected foodborne pathogens - Mohd Khairul, Nurul Shafiqa Atikah (2021)
Sugarcane molasses is thick, dark, and sweet syrup derived from the sugar refining process and teems with numerous essential elements. Sugarcane molasses have various valuable phenolic constituents such as flavonoids and melanoidins, generating antioxidant and antibacterial properties. The significantly high number of bioactive compounds from plant by-products lead to evaluate health conferred materials from sugarcane molasses. Since the application of synthetic preservatives has increased food safety crisis, the pressure on food manufacturers and adverse health impacts such as allergies, asthma, gastrointestinal problems and even cancers, sugarcane molasses can be introduced as a natural preservative in the food industry. Therefore, the objectives of this study were 1) to characterise the composition of sugarcane molasses, 2) to determine the antioxidant and antibacterial activities of sugarcane molasses ethanolic extract against selected foodborne pathogens, and 3) to investigate the bacteriostatic mechanisms of sugarcane molasses ethanolic extract towards Staphylococcus aureus and Escherichia coli. The composition of sugarcane molasses was determined by proximate analysis, sugar and amino acid profiling. Antioxidant activities were estimated by a total phenolic compound assay and a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Meanwhile, antibacterial activities were carried out using disc diffusion, minimum inhibition concentrations (MICs) and minimum bactericidal concentrations (MBCs) assays. Bradford assay, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analysis were carried out to analyse the bacteriostatic mechanisms and morphological changes of the bacterial cell. The proximate composition of sugarcane molasses consisted of 75.10±0.7% carbohydrate, 17.55±0.2% moisture, 5.35±0.1% ash, 2.00±0.4% crude protein and zero fat. It was also rich in sugar content included sucrose, fructose and glucose. Sugarcane molasses ethanolic extract showed high total phenolic compounds; phenylvaleric acid, quinic acid, tannic acid, apigenin and gallic acid with high antioxidant activities and 50% inhibitory concentration (IC50 value) was about 0.79 mg QE/g. The inhibition zone against four foodborne pathogens, Staph. aureus, Listeria monocytogenes, E. coli and Salmonella Typhimurium, ranged from 8.82±0.3 mm to 25.05±1.6 mm. Meanwhile, the MICs of sugarcane molasses ethanolic extract ranged from 3.125% to 6.25% v/v and MBCs were 6.25% to >12.5% v/v. These revealed the highest antibacterial activities were found in Gram-positive Staph. aureus and Gramnegative E. coli. The protein leakages of Staph. aureus and E. coli that treated with sugarcane molasses ethanolic extract were ranged from 1.91 μg to 2.53 μg and 1.09 μg to 2.29 μg, respectively. Results of SEM and TEM analysis suggested the cytoplasmic membranes of Staph. aureus and E. coli were damaged and ruptured. The sugarcane molasses ethanolic extract was found able to change the morphology of bacterial cells. In conclusion, sugarcane molasses is high in carbohydrate, mainly sucrose. They are also rich in phenolic compounds, which can be a potential source for antioxidant and antibacterial compounds.